The Contribution of Cultural Arts Production to Improving the Community’s Economy - Eka Mega Agustina (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2022)
There are more and more centers for cultural studies and collections of works of art that can later be used as works of art that can generate income and people's livelihoods. The purpose of this study was to describe the extent of the role of painting culture in the economy of the people of Kampung Giri Harja, Jelekong Village, Baleendah District, Bandung Regency. So it is useful to provide important information about the existence of Kampung Giri Harja, Jelekong Village, Bandung Regency, namely that besides being a center for cultural studies it can also make painting a source of economic income and employment for the Jelekong people and regional income. The research method used in this study is a descriptive analysis method using a qualitative approach—data collection, observation, interviews, and literature studies. The subject of this research is the arts village and its people. The results of the study show that the culture of painting in Giri Harja Village, Jelekong Village, Baleendah District, Bandung Regency can provide community welfare and a source of employment for the community around Giri Harja and migrants who enter Giri Harja Village. This is evidenced by the sufficient income earned by gallery owners, craftsmen and other artists. It is also proven that these paintings are not marketed at home as usual, but have been marketed outside areas such as Cipanas, Bogor, Jakarta and even galleries in Jakarta.